PENDAMPINGAN PENATAAN SISTEM ADMINISTRASI DESA DENGAN MENGEMBANGKAN APLIKASI ADMINISTRASI DESA TERPADU DI KELURAHAN ARJOSARI - Pramoedyo, Henny; Ngabu, Wigbertus; Wardhani, Ni Wayan Surya; Iriany, Atiek; Chairunissa, Abela (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to assist Kelurahan Arjosari in restructuring its administrative system more effectively and efficiently through the development of a village administration application built with Microsoft Excel and Visual Basic for Applications (VBA). Based on initial observations, the administrative processes in the kelurahan were still conducted manually, leading to slow public service delivery and a high risk of errors. The developed application is designed to integrate with the village's population database, automate the generation of documents based on National Identification Numbers (NIK), and provide automatic data validation features. Through Focus Group Discussions (FGD) and the official launching of the application, local officials were actively involved in the planning and training phases. Evaluation results show that the application is easy to use, accelerates the document service process, and improves administrative data accuracy. This initiative has had a positive impact on the quality of public services at the local level and serves as a model for applying simple but effective technology to support digital transformation in village governance